Elementary surface acoustic wave effects studied by scanning acoustic force microscopy - Hesjedal, T; Behme, G (2000)
Scanning Acoustic Force Microscopy (SAFM) has been used to study elementary surface acoustic wave phenomena with nanoscale spatial resolution. The SAFM technique is capable of detecting acoustic wave properties of arbitrarily polarized modes with sub-wavelength resolution and unmatched sensitivity. Elementary model systems like symmetric single finger wave sources and circular wave sources are studied for the first time in detail.